2018
DOI: 10.1051/matecconf/201816205019
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of soil polluted with Iraqi crude oil using grass plant

Abstract: Remediation technology is a promising technique that decreases pollutants like hydrocarbons from the environment. An experimental work was done at green house of University of Technology in order to study the effect of crude oil on the plant growth and to measure the decrement which happened on shoot height, germination rate and the reduction of total petroleum hydrocarbon (TPH), which resulted by this phytoremediation technique. The samples of soil were measured for TPH reduction and removal by Horiba model O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The role of plants in phytoremediation is not limited to heavy metals only, but can include other pollutants such as hydrocarbons. Al-Obaidy et al(2016) found that cotton plants have a significant role in reducing pollution by petroleum hydrocarbons in the soil . Mohamed et al (2021) found that the oleander plant has a high ability to accumulate heavy metals in its leaves, including lead and cadmium, and it can be used in the biological monitoring of heavy metal contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of plants in phytoremediation is not limited to heavy metals only, but can include other pollutants such as hydrocarbons. Al-Obaidy et al(2016) found that cotton plants have a significant role in reducing pollution by petroleum hydrocarbons in the soil . Mohamed et al (2021) found that the oleander plant has a high ability to accumulate heavy metals in its leaves, including lead and cadmium, and it can be used in the biological monitoring of heavy metal contamination.…”
Section: Resultsmentioning
confidence: 99%
“…Many plants are used to assess air water and soil pollution with heavy metals due to the property of their accumulation in the different parts of the plant, especially the leaves ( Belguidoum et al 2020;Vannucchi et al 2020) . Various methods have been used to reduce the concentrations of these elements in the environment, including phytoremediation, which uses plants to adsorb or absorb these elements from the air, water and soil (Al-Obaidy et al, 2016 ) . The concentrations of pollutants can be detected both from soil and atmospheric by trees as an effective bio monitors (Mohamed et al, 2021 ) .…”
Section: Introductionmentioning
confidence: 99%